(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Weight gain is a product of consuming more energy (calories) through food and beverage than you expand through the combination of what it takes to sustain the very basic function of life (resting metabolism),metabolizing the food we ingest (thermic effect of food) and what you burn in daily activities also known your exercise metabolic rate. A person can gain weight he or she consume more calories than needed to fuel these 3 things (regardless of if they come from Dietary fat, carbohydrates, protein, alcohol or mixture of nutrient. Public health recommendation for us population 1977 were to reduced fat intake to low as 30% of calories to lower the incidence of coronary artery disease. These recommendation results in a compositional shift in food materials in the agricultural industry and fractional content of fat was replaced principally with carbohydrates. Subsequently, high carbohydrate were recognized as contributing to the lipoprotein pattern that characteristic atherogenic dyslipidemia and hypertriacylglycerlemia the rising incidence of metabolic syndrome and obesity are becoming common themes in the literature. Current recommendation to keep saturated fatty acids, Trans fatty acid, and cholesterol intake as low as possible while consuming a nutritionally adequate diet. In the face of such recommendation the agricultural industry is shifting food composition towards the lower proportion of all saturated fatty acid